PENGARUH MODEL ARGUMENT DRIVEN INQUIRY (ADI) PADA MATERI MUTASI GEN TERHADAP KEMAMPUAN ARGUMENTASI ILMIAH DAN HASIL BELAJAR SISWA KELAS XII SMAN 17 GARUT - Bilqis Nurazizah; Dewi Hernawati; Chevi Ardiana Rusmawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Argument Driven Inquiry (ADI) model on genetic mutation material on students’ scientific argumentation ability and learning outcomes in class XII SMAN 17 Garut. The method used is quasi-experimental with a pretest-posttest control group design. The research subjects consisted of 34 students in the experimental class using the ADI model and 35 students in the control class using conventional learning. Research instruments included pretest-posttest questions to measure cognitive learning outcomes and an argumentation assessment rubric based on Toulmin’s Argument Pattern (TAP) with four argumentation quality levels. The results showed that the average pretest of the experimental class was 62.88, increasing to 78.18 in the posttest, with an N-Gain of 0.41 (moderate category). The control class obtained an average pretest of 56.89 and posttest of 69.17 with an N-Gain of 0.28 (low category). The scientific argumentation ability of the experimental class showed that most students were at Level 3 (55.9%) with an average score of 77.94 (SD = 14.20). The Shapiro-Wilk normality test showed normally distributed data (sig. 0.652 and 0.324 > 0.05), the Levene homogeneity test showed homogeneous data (sig. 0.960 > 0.05), the One-Way ANOVA test yielded F = 21.100 with sig. < 0.001, and the Independent Sample T-Test yielded sig. < 0.001 for both dependent variables. It can be concluded that the Argument-Driven Inquiry (ADI) model has a significant effect on students’ scientific argumentation ability and learning outcomes in genetic mutation material.